Pengaruh Intensitas Kebisingan terhadap Gangguan Pendengaran pada Pekerja di Indonesia: Meta-Analisis - Ilmidin, Ilmidin; Syaharuddin Nur; Petrus Yohanes Ismail Arwimbar; Rahmadani, Ulfa; Arisjulyanto, Dedy (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Noise in the workplace is one of the risk factors that can endanger the health and safety of workers. Noise exposure is commonly found in industrial areas such as factories, production machinery, and activities around airports. According to the World Health Organization (WHO), more than 430 million people worldwide suffer from hearing loss. This study aims to analyze the relationship and effect of noise exposure on hearing loss among workers in Indonesia. The research method employed is a systematic literature review with a meta-analysis approach, involving the stages of searching, screening, and analyzing data from relevant scientific articles. The results of the meta-analysis show a p-value of < 0.001, indicating a statistically significant association between noise exposure and hearing loss. The Odds Ratio (OR) value of 2.643 suggests that workers exposed to noise levels exceeding the Threshold Limit Value (TLV) are 2.6 times more likely to experience hearing loss compared to those who are not exposed or are exposed to noise levels below the TLV. The 95% Confidence Interval (CI) ranges from 1.513 to 4.610. Based on these findings, it is recommended that both workers and companies regularly measure noise levels, use hearing protection equipment, and conduct ongoing education and evaluations of workplace hazards.